Territorial Planning In Lithuania: The Issues of Security of Society and Interests of Investors - Birutė Pranevičienė; Kristina Šostakienė; Violeta Vasiliauskienė (Montenegrin Journal of Economics)
Territorial planning is a complex process which includes the formation of the directions of the development of the whole country and of a particular territory, the setting of priorities of the usage of a territory, limitations, the level and development of urbanization, and the establishment of the limits of the development of the activity of natural and legal persons. This article aims to analyse the theoretical and legal premises for the implementation of individual interest, for the defence of public interest, the assurance of public safety and the alignment of the interests of investors in the process of territorial planning. To reach the abovementioned aim such tasks for this article were set: to define the relationship between the individual interest and public interest during the process of territorial planning; to reveal the possibilities to ensure the security of society in the process of territorial planning; to provide insights for the alignment of the interests of investors, public interest and society interests in the process of territorial planning. The research was focused on Lithuanian territorial planning. In the course of reaching the objective of the research the methods of systemic, analytical-critical, and comparative analysis were employed. In addition, the methods of documentary analysis and generalization were used.